Effects of fodder banks on growth and survival of West African Dwarf goats under village conditions in subhumid Nigeria - Ikwuegbu, O.A.; Tarawali, G.; Rege, J.E.O. (Elsevier, 1995)
Thirty-two goat flocks belonging to 45 farmers and raised under village conditions in the Ganawuri area of the subhumid zone of Nigeria were monitored every 2 weeks for 30 months to determine productivity under village conditions. Records collected on kids included birth weight, birth type, body weight (BW), mortality and disposal information. In the wet season (August-October) goats were either tethered on natural pasture (NP) or were free-ranging on fodder banks (FB) of Stylosanthes spDuring the dry season, all animals were free-ranging on natural pasture (NP), forbs, crop residues or household wastes. Birth weight was affected (P<0.05) by year and season of birth, sex of kid and birth type. Both rate of gain and BW up to weaning (5 months) were affected (P<0.05) by year, parity and birth type. Animals on FB gained weight at a faster rate (33.8 vs. 28.9 g per day) between birth and 12 months of age and were consistently heavier than their counterparts on NP at all ages, but only the differences in BW at 3 months (5.1 vs. 4.6 kg) and 12 months (14.1 vs. 12.0 kg) of age were significant (P<0.01). Additionally, FB animals suffered less weight loss than NP animals during periods of limited feed availability. Overall mortality to 12 months of age was 14.5 percent and this represented 45 percent of animal disposals from these flocks. There was no difference in mortality between FB and NP flocks. Peak wet season was associated with the highest mortality and this was attributed mainly to increased parasite challenge during this period. Results of the study indicated potential contribution of FB for the improvement of growth performance of village goats in situations where, due to limited land, free-ranging is limited during the cropping season.